2011
DOI: 10.3345/kjp.2011.54.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic gastrostomy in children

Abstract: PurposePercutaneous endoscopic gastrostomy (PEG) can improve nutritional status and reduce the amount of time needed to feed neurologically impaired children. We evaluated the characteristics, complications, and outcomes of neurologically impaired children treated with PEG.MethodsWe retrospectively reviewed the records of 32 neurologically impaired children who underwent PEG between March 2002 and August 2008 at our medical center. Forty-two PEG procedures comprising 32 PEG insertions and 10 PEG exchanges, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…The 5% incidence of early major complication is similar to the rate of incidence found in other published reports from this institution [20,22] and is similar to a meta-analysis by Wollman et al (5.9%) [27]. The minorcomplication rate (21%) and overall complication rate in this study (total of early and late, major and minor, 27%), compares favourably with that of other reports of children undergoing different methods of insertion (11.7-73%) [20,22,23,25,26,28]. Tube maintenance issues of blockages, dislodgement, leak, malfunction, etc., are also common amongst all gastrostomy tube types [20,22,28].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The 5% incidence of early major complication is similar to the rate of incidence found in other published reports from this institution [20,22] and is similar to a meta-analysis by Wollman et al (5.9%) [27]. The minorcomplication rate (21%) and overall complication rate in this study (total of early and late, major and minor, 27%), compares favourably with that of other reports of children undergoing different methods of insertion (11.7-73%) [20,22,23,25,26,28]. Tube maintenance issues of blockages, dislodgement, leak, malfunction, etc., are also common amongst all gastrostomy tube types [20,22,28].…”
Section: Discussionsupporting
confidence: 94%
“…The mean age at G-tube insertion in this group with PRS was 66 days (range 7-167 days, median 60 days) and mean weight 4.27 kg (range 1-7 kg, median 4.3 kg) compared to a mean age 3.9 years (range 1 day-23 years, median 1.53 years) and weight 13.4 kg (range 1-77 kg, median 8.6 kg) of our total population referred for a G-tube at this institution (unpublished data). This patient population is also younger and smaller than the mean age and weight of other pediatric reports in the literature [22][23][24][25][26]. Despite these demographics, the high technical success rate of radiologically placed G-tube insertions in this study (100%) is similar to that found in a meta-analysis by Wollman et al [27] of 99.2% for radiologically placed G-tubes, and compares well to the rate of 95% for PEG and 98.5% placed by laparoscopy [23].…”
Section: Discussionmentioning
confidence: 87%
“…PEG placement is a common indication for endoscopy of the upper gastrointestinal tract (Park et al, 2011;Srinivasan et al, 2009), and is now much more widely used than surgical or radiological insertion. Rates of PEG insertion have risen in recent years: in 1989, 15,000 PEG tubes were placed; in 1995, 121,000 PEG tubes were placed, and in 2000, more than 216,000 tubes were inserted for feeding (Delegge, 2008;Grant et al, 1998;Roche, 2003;Duszak & Mabry, 2003).…”
Section: Percutaneous Endoscopic Gastrostomymentioning
confidence: 99%
“…Neurogenic indications for gastrostomy include dysphagia from a variety of causes, including stroke, brain injury, cerebral palsy, brain tumors, HIV encephalopathy, neonatal encephalopathy, and neurodegenerative syndromes; non-neurological indications include such conditions as head and neck cancer, surgery to the mouth and throat, aspiration, Crohn's disease, severe burns, and decompression of the stomach in obstructing intraabdominal malignancy (Buchholz, 1994;Laasch et al, 2003;Nishiwaki et al, 2009;ElMatary, 2008;Naik et al, 2009;Park et al, 2011). The most common indication for PEG in children and adults is neurogenic dysphagia (El-Matary, 2008;Miller et al, 1989;Nicholson et al, 2000;Friedman et al, 2004;Srivastava et al, 2005).…”
Section: Indications For Percutaneous Endoscopic Gastrostomymentioning
confidence: 99%
“…In the past, surgical gastrostomy was used, but this procedure is highly invasive and is associated with numerous potential complications. 1 Since the first published report of a percutaneous endoscopic gastrostomy (PEG) in 1980 by Gauderer and Ponsky, 2 the procedure has been modified and improved several times. It has now replaced the surgical gastrostomy which was associated with a markedly higher rate of complications.…”
Section: Introductionmentioning
confidence: 99%